PELATIHAN PENGUATAN KOMPETENSI KARAKTER ÛLÛ AL-ALÂB BERBASIS AL-QUR’AN MENUJU INDONESIA EMAS PADA TAHUN 2045 DI YAYASAN BALQIS - Ahmad Husnul Hakim; Asep Muksin; Mohamad Zaenal Arifin; Faridatun Nisa; Ahmad Zain Sarnoto; Esse Esse (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study tries to reveal that the character of ûlu al-Albâb which Allah has indicated in several of his words in the Qur'an describes a superior human being, insan kamil and plenary, a generation that has spiritual intelligence, social intelligence and social intelligence that can lead Indonesia to Indonesia gold in 2045. This conclusion is based on the study and the author's findings on several verses of the Qur'an that hint at superior human beings, and one of them is expressed by the word lu ûlu al-Albâb which can be found 16 times in repetition on 10 a letter which as a whole begins with the words lu or li. The method used in this research is a qualitative analysis method through library research with an interpretive descriptive approach